The capacity of young national medicine regulatory authorities to ensure the quality of medicines: case of Rwanda - Jean Baptiste B. Shabani; Egide Kayitare; Eric Nyirimigabo; Vedaste Habyalimana; Marilyn M. Murindahabi; Lazare Ntirenganya; Clarisse Irasabwa; Eugene Rutungwa; Jose Edouard Munyangaju; Innocent Hahirwa (Journal of Pharmaceutical Policy and Practice, 2022)
Background Access to quality medicines is a global initiative to ensure universal health coverage. However, the limited capacity of National Medicines Regulatory Authorities (NMRAs) to prevent and detect the supply of poor-quality medicines led to the predominance of sub-standard and falsified (SF) medicines in the supply chains of many countries. Therefore, this study was designed to assess the capacity of a young NMRA to ensure the quality of medicines with Rwanda as a case study. Objective This study aimed to assess the capacity of the Rwanda FDA, a young NMRA, to identify gaps and existing opportunities for improving regulatory capacity and ensuring the quality of medicines. Methods This study used a descriptive cross-sectional design with both quantitative and qualitative approaches. The quantitative approach used a self-administered questionnaire to collect data from employees of Rwanda FDA who are involved in medicine regulatory practices based on their positions while the qualitative research approach covered a desk review of key regulatory documents. The data collection tool was developed from the World Health Organization (WHO) Global Benchmarking Tool (GBT) for “Evaluation of National Regulatory System of Medical Products Revision VI”. Results Of the 251 WHO sub-indicators assessed, 179 sub-indicators (71%) were fully implemented, 17 sub-indicators (7%) were partially implemented, 9 sub-indicators (4%) were ongoing and 46 sub-indicators (18%) were not implemented by the time of the study. The results of the study showed that the estimated maturity level at which Rwanda FDA operates is maturity level 2. The study reported the challenges hindering the implementation of key regulatory functions that need to be addressed. Challenges reported include but are not limited to understaffing, lack of automation system, poor implementation of the quality management system, lack of screening technologies for SF medicines, low capacity of the quality control laboratory to test all sampled medicines and lack of regulatory inspection tools/equipment. Conclusion Findings indicated that all key regulatory functions were operating and supported by the legal framework. However, the implementation of key regulatory functions faced challenges that need to be addressed for better organizational effectiveness and compliance with the requirements of a higher maturity level.